Developing process approach-based reading textbook for grade IV students - Dedy Irawan (Jurnal Prima Edukasia, 2017)
The objective of this research and development study is generating approach-based reading textbook which will be appropriate and feasible for implementation in order to improve the reading skills of Grade IV students. This research and development study referred to the steps of research and development proposed by Borg Gall. The subjects in this study were the Grade IV students from the State Elementary Schools under the Regional Unit of Technical Implementation in Kutasari District, the Regency of Purbalingga which consist of SD Negeri 1 Cendana, of SD Negeri 1 Karangjengkol, SD Negeri 1 Sumingkir, and SD Negeri 2 Munjul. In gathering the data, the researcher made use of interview, document analysis, rating scale, test, and questionnaire. The results of this research and development study are a process approach-based reading textbook for Theme 9 “My Food is Healthy and Nutritious” which has been designed in five reading activities namely: (1) setting up; (2) reading; (3) responding; (4) understanding; and (5) expanding the understanding. This textbook has been considered feasible for implementation according to the material expert and the media expert with “Good” category and according to the book design expert with “Very Good” category. There are differences in the final results between the experimental group and the control group after the approach based-reading textbook has been applied with the significance 0.05. These differences show the significant reading skills improvement with sig. value (2-tailed) = 0.024.